Malignant transformation of actinic keratoses to squamous cell carcinoma in an albino - Ramalingam Vijaya; Sinnakirouchenan Ramapriya; Thappa Devinder (Wolters Kluwer Medknow Publications, 2009)
A 25-year-old male, who was a known case of oculocutaneous albinism presented to us with right inguinal swellings of six months′ duration. He gave a preceding history of a similar lump in the right thigh, which was excised at the Chennai Government Hospital. He was diagnosed to have oculocutaneous albinism with actinic keratoses, with multiple squamous cell carcinomas (with metastatic deposits in the right inguinal region) and cutaneous horns. The case is reported to highlight preventive aspects in the management of albinos.